1988
DOI: 10.1148/radiology.169.2.3174982
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic carcinoma: staging with MR imaging at 1.5 T.

Abstract: Magnetic resonance (MR) imaging was used to stage prostatic carcinoma in 81 patients with a proved diagnosis. MR imaging findings were correlated with histologic findings regarding the local extent of disease (37 patieNts) and the presence of nodal metastases (51 patients). Tumor nodules were detected in the peripheral zone (PZ) in 34 of 37 patients and were of low signal intensity compared with the signal of the PZ. Hemorrhage in the PZ represented a problem in tumor detection and in tumor volume measurement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(55 citation statements)
references
References 0 publications
4
45
1
5
Order By: Relevance
“…It was confirmed that tu mors located ventrally and centrally in histopathologic specimens were Tumor volume is a predictor of pathologic stage (22). Except for one study performed with an externalarray coil (23), studies performed with endorectal coil (13) and body coil MR imaging (24)(25)(26)(27) reported a poor cor relation between MR tumor volume and the volume as calculated from the pathologic specimen. Mirowitz et al (6) who studied postcontrast Tlweighted images also reported poor correlation between the estimated and calculated volume.…”
Section: Discussionmentioning
confidence: 87%
“…It was confirmed that tu mors located ventrally and centrally in histopathologic specimens were Tumor volume is a predictor of pathologic stage (22). Except for one study performed with an externalarray coil (23), studies performed with endorectal coil (13) and body coil MR imaging (24)(25)(26)(27) reported a poor cor relation between MR tumor volume and the volume as calculated from the pathologic specimen. Mirowitz et al (6) who studied postcontrast Tlweighted images also reported poor correlation between the estimated and calculated volume.…”
Section: Discussionmentioning
confidence: 87%
“…IN PROSTATE IMAGING, anatomical details are excellently depicted by MRI using T2-weighted rapid acquisition with relaxation enhancement (RARE) (also known as T2W-TSE or T2W-FSE), which has been the gold standard (1,2).…”
mentioning
confidence: 99%
“…[15][16][17][18] As a result, an endorectal coil was developed to better visualize the zonal architecture of the prostate and tumour in the periprostatic tissue and SVs. 19 Engelbrecht and colleagues found endorectal coil superiority in their meta-analysis, however, a similar systematic review revealed no difference between body and endorectal coil images.…”
Section: Discussionmentioning
confidence: 99%